TELAAH METODE INQUIRY LEARNING DALAM MEMBANGUN KETERAMPILAN BERPIKIR KRITIS SISWA SEKOLAH DASAR: ANALISIS FILSAFAT RASIONALISME DESCARTES - Ulya, Helmy Zulfikar; Putri, Mufida Awalia; Wahyuningsih, Ika (Auladuna: Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The purpose of this study is to find out how the inquiry learning method can build critical thinking skills of elementary school students from the perspective of Descartes' philosophy of rationalism. This study uses a qualitative descriptive method with a literature study approach. Data collection techniques through documentation and text analysis. Documentation is done by collecting appropriate literature sources. Data analysis uses content analysis. The results of the study show that the inquiry learning method has integrated the critical thinking process. The inquiry learning stage has a similar process to Descartes' rationality stage. Thus, the principles-pronance of Descartes' rationalist philosophy became the basis of the inquiry learning method in building critical thinking skills of elementary school students.